Symptomatic Improvement, Increased Life-Span and Sustained Cell Homing in Amyotrophic Lateral Sclerosis After Transplantation of Human Umbilical Cord Blood Cells Genetically Modified with Adeno-Viral Vectors Expressing a Neuro-Protective Factor and a Neural Cell Adhesion Molecule - Robertovich Islamov, Rustem; Anatolyevich Rizvanov, Albert; Alexandrovich Mukhamedyarov, Marat; Ildusovich Salafutdinov, Ilnur; Evgenevna Garanina, Ekaterina; Yuryevna Fedotova, Valeria; Vladimirovna Solovyeva, Valeria; Olegovna Mukhamedshina, Yana; Zufarovich Safiullov, Zufar; Alexandrovich Izmailov, Andrey; Sergeevna Guseva, Daria; Lvovich Zefirov, Andrey; et al. (Current Gene Therapy, 2015)
Amyotrophic lateral sclerosis (ALS) is an incurable, chronic, fatal neuro-degenerative disease characterized by progressive loss of moto-neurons and paralysis of skeletal muscles. Reactivating dysfunctional areas is under earnest investigation utilizing various approaches. Here we present an innovative gene-cell construct aimed at reviving inert structure and function. Human umbilical cord blood cells (hUCBCs) transduced with adeno-viral vectors encoding human VEGF, GDNF and/or NCAM genes were transplanted into transgenic ALS mice models. Significant improvement in behavioral performance (open-field and grip-strength tests), as well as increased life-span was observed in rodents treated with NCAM-VEGF or NCAM-GDNF co-transfected cells. Active trans-gene expression was found in the spinal cord of ALS mice 10 weeks after delivering genetically modified hUCBCs, and cells were detectable even 5 months following transplantation. Our gene-cell therapy model yielded prominent symptomatic control and prolonged life-time in ALS. Incredible survivability of xeno-transpanted cells was also observed without any immune-suppression. These results suggest that engineered hUCBCs may offer effective gene-cell therapy in ALS.
Keywords: neural cell adhesion molecule (NCAM)